Modulation of mitochondrial respiration rate and calcium-induced swelling by new cromakalim analogues. (1st November 2020) - Mouithys-Mickalad, Ange; Ceusters, Justine; Charif, Mounia; El Moualij, Benaïssa; Schoumacher, Mathieu; Plyte, Simon; Franck, Thierry; Bettendorff, Lucien; Pirotte, Bernard; Serteyn, Didier; de Tullio, Pascal
Abstract: A cellular model of cardiomyocytes (H9c2 cell line) and mitochondria isolated from mouse liver were used to understand the drug action of BPDZ490 and BPDZ711, two benzopyran analogues of the reference potassium channel opener cromakalim, on mitochondrial respiratory parameters and swelling, by comparing their effects with those of the parent compound cromakalim. For these three compounds, the oxygen consumption rate (OCR) was determined by high-resolution respirometry (HRR) and their impact on adenosine triphosphate (ATP) production and calcium-induced mitochondrial swelling was investigated. Cromakalim did not modify neither the OCR of H9c2 cells and the ATP production nor the Ca-induced swelling. By contrast, the cromakalim analogue BPDZ490 (1) induced a strong increase of OCR, while the other benzopyran analogue BPDZ711 (2) caused a marked slowdown. For both compounds, 1 displayed a biphasic behavior while 2 still showed an inhibitory effect. Both compounds 1 and 2 were also found to decrease the ATP synthesis, with pronounced effect for 2, while cromakalim remained without effect. Overall, these results indicate that cromakalim, as parent molecule, does not induce per se any direct effect on mitochondrial respiratory function neither on whole cells nor on isolated mitochondria whereas both benzopyran analogues 1 and 2 display totally opposite behavior profiles, suggesting that compound 1, by increasing the maximal respiration capacity, might behave as a mild uncoupling agent and compound 2 is taken as an inhibitor of the mitochondrial electron-transfer chain. Highlights: New cromakalim analogues inhibit mitochondrial respiration rate with low toxicity. Benzopyran derivatives inhibit the Calcium-induced swelling of mitochondria. Cromakalim per se does not act on respiration rate and swelling of mitochondria. Benzopyran derivatives decrease the ATP synthesis. BPDZ490 behaves as a mild uncoupling agent and BPDZ711 as a strong inhibitor.